Regulation of a Chitinase Gene Promoter by Ethylene and Elicitors in Bean Protoplasts - Roby, Dominique (1991)
Chitinase gene expression has been shown to be transcriptionally regulated by a number of inducers, including ethylene, elicitors, and pathogen attack. To investigate the mechanism(s) responsible for induction of chitinase gene expression in response to various stimuli, we have developed a transient gene expression system in bean (Phaseolus vulgaris) protoplasts that is responsive to ethylene and elicitor treatment. This system was used to study the expression of a chimeric gene composed of the 5′ flanking sequences of a bean endochitinase gene fused to the reporter gene β-glucuronidase linked to a 3′ fragment from nopaline synthase. Addition of 1-aminocyclopropane-1-carboxylic acid, the direct precursor of ethylene, or elicitors such as chitin oligosaccharides or cell wall fragments derived from Colletotrichum lagenarium, to transformed protoplasts resulted in a rapid and marked increase in the expression of the chimeric gene. The kinetics and dose response for these treatments were similar to those observed for the native gene in vivo. Analyses of 5′ deletion mutants in the protoplast system indicated that DNA sequences located between −305 and −236 are important for both ethylene and elicitor induction of the reporter gene.